PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Ananda Tri Astuti Riatma; Ferinaldi; Ade Susanti S.Pd., M.Pd (Hiradika | Hira Institute, 2025)
This inquiry was prompted by the need for students’ numerical reasoning abilities. The purpose of this investigation is to assess and depict students’ numerical reasoning abilities using the Creative Problem-Solving learning demonstration, which is more effective than traditional learning for students in lesson IX at Junior Tall School in Nation 14 Merangin for the 2024/2025 academic year. The strategy employed in this investigation is a test strategy with a population of all Lesson IX students at Junior Tall School within Nation 14 Merangin for the 2024/2025 academic year. The test was administered using the Basic Irregular Testing procedure, which employed a lottery; the instrument used was a test. Information examination procedures utilize typicality tests, homogeneity tests, and speculation tests. Based on the inquire about comes about of speculation testing using the t test, tcount > ttable or 2.298 > 1.687 based on the right-hand test choice criteria, H1 is acknowledged, which suggests that the capacity to fathom scientific issues utilizing the Inventive Problem Solving learning demonstrate is way better than customary learning for lesson IX understudies at Junior Tall School within the Nation 14 Merangin 2024/2025 scholarly year.